Penghambatan Korosi Melalui Adsorpsi Ekstrak Kulit Kakao (Theobroma cacao) pada Permukaan Baja: Metode Eksperimen dan DFT - Apriska Prameswari; Dahyunir Dahlan; Yuli Yetri; Imelda (Universitas Andalas, 2023)
Steel surface coating has been carried out using the immersion method in an inhibitor of cacao (Theobroma cacao) peel extract for 24, 72, 120, and 168 hours. The corrosion treatment was performed using HCl with different immersion time of 48, 96, and 144 hours after coating process with the inhibitor. Corrosion testing with the weight loss method gave the best results with the lowest corrosion rate of 0.2972 mg.cm2/hour and inhibition efficiency of 74.7128% for steel samples with the longest immersion time in inhibitor. Optical microscopy and SEM images indicated that the longer the immersion time in the inhibitor, the better (i.e., fewer holes and cracks) the surface morphology of the steel. The appearance of four sharp peaks in the XRD diffractogram indicated that the samples with the lowest corrosion rate produced Fe and C crystalline phases due to the reaction between the steel surface and the inhibitor. A quantum chemical analysis using the DFT (Density Functional Theory) method also produced a fairly high inhibition efficiency and was close to the experimental results of 80.2098%.